2009
DOI: 10.1136/sti.2008.033985
|View full text |Cite
|
Sign up to set email alerts
|

Reported number of sexual partners: comparison of data from four African longitudinal studies

Abstract: Objective: To compare reported numbers of sexual partners in Eastern and Southern Africa. Methods: Sexual partnership data from four longitudinal population-based surveys (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) in Zimbabwe, Uganda and South Africa were aggregated and overall proportions reporting more than one lifetime sexual partner calculated. A lexis-style table was used to illustrate the average lifetime sexual partners by site, sex, age group and birth cohort. The male-to-female ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 30 publications
7
35
0
Order By: Relevance
“…Data from five cohorts in Uganda, Zimbabwe and South Africa indicates that the majority of ‘younger old’ men and a considerable minority of women aged 40-60 years remained sexually active. 8 Data from ‘older old’ adults in Southwestern Nigeria shows that around a quarter of adults aged 65-102 had extra-marital sex at least once since turning 65. 9 Furthermore, several studies have shown that older adults are less likely to use condoms than younger age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Data from five cohorts in Uganda, Zimbabwe and South Africa indicates that the majority of ‘younger old’ men and a considerable minority of women aged 40-60 years remained sexually active. 8 Data from ‘older old’ adults in Southwestern Nigeria shows that around a quarter of adults aged 65-102 had extra-marital sex at least once since turning 65. 9 Furthermore, several studies have shown that older adults are less likely to use condoms than younger age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Although monogamous relationships are the most common relationships between a man and a woman, evidence suggests that many sexually active people, including those in sub-Saharan Africa, have more than one sexual partner (Morris & Kretzschmar, 1997; Todd et al, 2009). For instance, in one study, conducted in five urban communities in sub-Saharan Africa, 26.5% of men and 14.4% of women reported being involved in multiple relationships (Lagarde et al, 2001).…”
mentioning
confidence: 99%
“…18 35 38 39 42 43 The gender-specific HIV transmission probability estimates per vaginal and anal act and the relative increase in HIV acquisition risk during RAI (RR RAI =4 to 20) (online Appendix C) are based on meta-analyses of observational studies 11–14. The limited data on HIV risk per insertive anal intercourse (IAI) indicate a lower risk than for RAI 10 11 14.…”
Section: Methodsmentioning
confidence: 99%